Family Food Security and Children’s Environment: A Comprehensive Analysis with Structural Equation Modeling - Wan Mohamed Radzi, C.W.J.; Hui, H.; Mohamed, N.A.; Jenatabadi, H.S. (MDPI, 2017)
Structural Equation Modeling (SEM) has been used extensively in sustainability studies to model relationships among latent and manifest variables. This paper provides a tutorial exposition of the SEM approach in food security studies and introduces a basic framework based on family food security and children's environment sustainability. This framework includes family food security and three main concepts representing children's environment, including children's BMI, health, and school performance. A detailed description is provided of how SEM is applied in this type of study. The proposed model contains dependent, independent, mediator, and moderator variables. Three latent variables categorized include family food security, children's health, and children's school performance, and two manifest variables are children's body mass index and children's gender. The samples for this study involve 452 Chinese children aged 7-12. The data analysis outcome indicates that the introduced model is capable of estimating the impact of family food security on children's environment. The results from this study confirm that the combination of children's body mass index with children's health acts as a strong mediator in the relationship between family food security and children's school performance.